Multidisciplinary Rehabilitation of Ectodermal Dysplasia: A Case Report - Gupta, Alka; Karki, Sunita; Thapa, Deepak; Shrestha, Rabindra Man (Orthodontic Journal of Nepal, 2016)
This case report describes a joint multidisciplinary approach of restoring function and esthetics in an 18-year-young female with ectodermal dysplasia. Ectodermal dysplasia is both physically and emotionally devastating to patients with dental manifestations. It is important that they are treated at an early age to help their social interaction. With proper dental intervention, the quality of life can be improved for patients with ectodermal dysplasia